Do Palestinian Lives Matter in Teacher Education? Centering an Anti-Zionist Commitment in (Early Childhood) Teacher Education - Padía, Lilly (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
Many self-proclaimed “social justice” teacher educators remained silent on Palestine prior to, during and following October 7th, 2023, citing ‘not knowing enough about the conflict’ to absolve themselves of the responsibility of addressing the genocide–and the ongoing settler colonial apartheid state. In teacher education, this compulsory Zionism is particularly troubling, especially for teacher education programs and faculty who claim to follow the foundations of critical race theory and culturally sustaining pedagogies. This tension begs the question: Do Palestinian Lives Matter in Teacher Education? I explore instances of compulsory Zionism in teacher education institutions and introduce teacher candidates’ quotes to demonstrate why this compulsory Zionism is harmful to us all. Building on FaithCrit (the intersections of Faith and Critical Race Theory in Education) to conduct an autoethnographic analysis, I introduce a teaching framework I call ‘Pedagogical Integrity’ to demonstrate how teacher educators can implement anti-Zionist turns in teacher education–and why it is imperative that we must engage them.